2019
DOI: 10.1111/cei.13367
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia: host susceptibility and shared genetics with pulmonary function and other traits

Abstract: Pneumonia is a common and severe infectious lung disease. Host genetics, together with underlying medical and lifestyle conditions, determine pneumonia susceptibility. We performed a secondary analysis of the results of two genome-wide studies for pneumonia in 23andMe participants (40 600 cases/90 039 controls) (Tian et al., 2017) and UK Biobank (BB) participants (12 614 cases/324 585 controls) (via the Global Biobank Engine) and used the GTEx database to correlate the results with expression quantitative trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…In this regard, HLA-C genetic variants are known to be associated with COVID-19 clinical outcome [37] , [38] , [39] , [40] . Importantly for the natural history of COVID-19 infection, GWAS have also shown that HLA-C constitutes a susceptibility locus for human pneumonia [ 65 , 66 ]. Similar links between the other candidate epigenetic targets identified here and immune imbalance associated with lung inflammation can be found, such as the case of IFI44L, which is overexpressed in the bronchoalveolar lavage of severe COVID-19 patients [67] and SARS-CoV-2-infected bronchial epithelial cells [68] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, HLA-C genetic variants are known to be associated with COVID-19 clinical outcome [37] , [38] , [39] , [40] . Importantly for the natural history of COVID-19 infection, GWAS have also shown that HLA-C constitutes a susceptibility locus for human pneumonia [ 65 , 66 ]. Similar links between the other candidate epigenetic targets identified here and immune imbalance associated with lung inflammation can be found, such as the case of IFI44L, which is overexpressed in the bronchoalveolar lavage of severe COVID-19 patients [67] and SARS-CoV-2-infected bronchial epithelial cells [68] .…”
Section: Discussionmentioning
confidence: 99%
“…high for the inhibiting KIR (KIR2DL1) than the activating KIR [functional KIR2DS4 ( 52 )], may cause NK cell hyporesponsiveness since the early phase of infection ( 49 ). As NK cells are at the forefront of antiviral response, particularly at that of the respiratory system ( 53 ), NK hyporesponsiveness may delay SARS‐CoV‐2 viral recognition and, subsequently, generate an inadequate immune response, supporting the virus propagation and lung damage, such as seen in severe pneumonia with a genetically predicted HLA-C low expression ( 54 ). A series of genetic studies with a Sardinian/Italian sample potentially support this hypothesis, by reporting a significantly high prevalence of both, HLA-C*04:01 allele and NK-cell inhibitor KIR2DL1 receptor, in COVID-19 cases ( 34 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…c4a is known as an allergenic toxin gene that produces an antimicrobial peptide and a mediator of local inflammation. Previous studies suggested that C4bp and C4a were associated with lung inflammation and injury (56,57).…”
Section: Discussionmentioning
confidence: 92%